Determination of 3.5-dinitro-N'-(5-nitrofurfurylidene) salicylic acid hydrazide in fish using immunochromatographic strip tests. Issue 1 (1st January 2019) - Meng, Xiangren; Ji, Dejun; Zhang, Wei; Fu, Lixia; Wang, Hengpeng; Wu, Peng
ABSTRACT: The nitrofurans were recently banned from use in livestock production due to their potential carcinogenicity in humans. Therefore, the screening of foods from animal origins for nitrofurans became mandatory. A rapid, specific and sensitive method based on immunochromatographic strip test has been developed for the determination of 3.5-dinitro- N' -(5-nitrofurfurylidene) salicylic acid hydrazide (DNSH) residues in fish. Fish samples were prepared by ultrasonic bath extraction, centrifugation, filtration, drying and res-suspension. The antigen (DNSH-glutaraldehyde-ovalbumin) and a goat anti-mouse IgG antibody were drawn onto a nitrocellulose membrane as the test and control line, respectively. Under optimal conditions, the DNSH cut-off limits for the test strips were determined as 10 ng/mL in 0.01 M phosphate buffered saline and 25 ng/mL in fish samples, with results obtained within 5min. Our data suggests this immunochromatographic assay can be used for the sensitive, rapid, and specific on-site screening of DNSH in fish products.